Pelatihan Penggunaan Formulasi Excel Untuk Pendataan Administrasi Pada UKKT Mampang Prapatan Jakarta - Pudjiarti, Eni; Rudianto, Biktra; Faizah, Siti; Sofica, Verra (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2023)
The use of computer applications almost all office work requires it.The development of technology, especially computer applications today is very helpful in administrative data processing, so that the data obtained can be arranged neatly and easy to understand. One of them is administrative data processing at UKKT RW.06 which requires an application that supports so that the data displayed can be understood because currently some of the administrative data displayed is still fairly manual, use of Microsoft Office applications, especially Ms. Excel on Coral data processing. The cadets are still not being used optimally because some of the Karang Taruna administrators still do not understand the use of the application used. Microsoft Excel itself is a software application that is used to process, store, and combine data in the form of formulas. Data that can be processed, namely, digital data in the form of calculation results and diagrams. This software has a special role in office area. Matters related to office data will be processed as well stored briefly and in detail in Microsoft Excel. The method used in provide education about the basic use of formulas in Microsoft Excel carried out by holding workshops on community service activities so that participants consisting of Karang Taruna administrators who will process administrative data UKKT RW.06 will be more familiar with the use of the Microsoft Excel Application for help process administrative data to make it more neat and easy to understand.